A Min–Max multiregulator system with stability analysis for aeroengine propulsion control. (February 2019) - Imani, Amin; Montazeri-Gh, Morteza
Abstract: Stability analysis is an essential issue in Min–Max multiregulator control strategy for commercial aircraft engines. In this paper, a Min–Max selector scheme along with a stability analysis method is provided for aeroengine propulsion control. It is assumed that the main regulator is a dynamic compensator and the limit regulators are constant gains. The regulators are determined in such a way that the individual control loops are stable. However, due to the switching nature of Min–Max structure, the stability of single loops does not necessarily ensure the overall system stability. In order to analyze the stability of the presented Min–Maxapproach, the architecture of the control system is transformed into the canonical form of Lure's system and the condition for absolute stability is specified using Multivariable Circle Criterion. The theoretical results can also be applied to investigate the stability of min-only or max-only schemes. Afterwards, using the provided methodology, the global asymptotic stability is proved for the control system of a high bypass two-spool turbofan engine and the performance of the designed Min–Max controller in tracking a desired fan speed and limit protection in fault-free and fault tolerant situations is compared with the well-known Min–Max/SMC approach. Highlights: A Min–Max selector controller along with a stability analysis method is presented. Structure of the control system is transformed into the form of Lure's system . Theoretical results can be applied to analyze the stability of min-only or max-only. Global asymptotic stability is proved for the control system of a turbofan engine. Simulations show the efficient performance of the presented Min–Max controller.